A deep-sea, high-speed, stereoscopic imaging system for in situ measurement of natural seep bubble and droplet characteristics. (October 2015) - Wang, Binbin; Socolofsky, Scott A.
Abstract: Development, testing, and application of a deep-sea, high-speed, stereoscopic imaging system are presented. The new system is designed for field-ready deployment, focusing on measurement of the characteristics of natural seep bubbles and droplets with high-speed and high-resolution image capture. The stereo view configuration allows precise evaluation of the physical scale of the moving particles in image pairs. Two laboratory validation experiments (a continuous bubble chain and an airstone bubble plume) were carried out to test the calibration procedure, performance of image processing and bubble matching algorithms, three-dimensional viewing, and estimation of bubble size distribution and volumetric flow rate. The results showed that the stereo view was able to improve the individual bubble size measurement over the single-camera view by up to 90% in the two validation cases, with the single-camera being biased toward overestimation of the flow rate. We also present the first application of this imaging system in a study of natural gas seeps in the Gulf of Mexico. The high-speed images reveal the rigidity of the transparent bubble interface, indicating the presence of clathrate hydrate skins on the natural gas bubbles near the source (lowest measurement 1.3 m above the vent). We estimated the dominant bubble size at the seep site Sleeping Dragon in Mississippi Canyon block 118 to be in the range of 2–4 mm and the volumetric flow rate to be 0.2–0.3 L/min during our measurements from 17 to 21 July 2014. Highlights: A deep-sea, high-speed, stereo imaging system is developed to study natural seep bubbles/droplets. The imaging system allows precise measurement of particle size while mounted on a ROV. Clathrate hydrate formation on natural gas bubbles was evaluated using high-speed imaging. The imaging system has been successfully deployed to study two seep sites in the Gulf of Mexico.